Adipose Mesenchymal Stem Cells Isolated after Manual or Water-jet-Assisted Liposuction Display Similar Properties - Bony, Claire; Cren, Mailys; Domergue, Sophie; Toupet, Karine; Jorgensen, Christian; Noël, Danièle (Frontiers in Immunology, 2016)
Mesenchymal stem or stromal cells (MSC) are under investigation in many clinical trials for their therapeutic potential in a variety of diseases, including autoimmune and inflammatory disorders. One of the main sources of MSCs is the adipose tissue, which is mainly obtained by manual liposuction using a cannula linked to a syringe. However, in the last years, a number of devices for fat liposuction intended for clinical use have been commercialized but few papers have compared these procedures in terms of stromal vascular fraction (SVF) or adipose stromal cells (ASC). The objective of the present study was to compare and qualify for clinical use the adipose stromal cells (ASC) obtained from fat isolated with the manual or the Bodyjet® waterjet-assisted procedure. Although the initial number of cells after collagenase digestion was higher with the manual procedure, both the percentage of dead cells, the number of CFU-F and the phenotype of cells were identical in the SVF at isolation and in the ASC populations at day 14. We also showed that the osteogenic and adipogenic differentiation potentials of ASCs were identical between preparations while a slight but significant higher in vitro immunosuppressive effect was observed with ASCs isolated from fat removed with a cannula. The difference in the immunomodulatory effect between ASC populations was however not observed in vivo using the delayed-type hypersensitivity model. Our data therefore indicate that the procedure for fat liposuction does not impact the characteristics or the therapeutic function of ASCs.